Tantangan Implementasi UU Pelindungan Data Pribadi Bagi Investor Asing di Indonesia - Bahary, Fajar Salas (SENTRI: Jurnal Riset Ilmiah, 2025)
As a developing country, Indonesia is also undergoing a shift toward digitalization. The digital transformation taking place within the government and society has led to changes in social behavior, particularly in transaction patterns and the management of personal data. Previously, Indonesia did not have specific legislation regulating the protection of personal data in the digital sphere. With the enactment of Law Number 27 of 2022 on Personal Data Protection (PDP Law), it is expected that the provisions within this law will serve as a legal framework for securing personal data. However, the implementation of the PDP Law still faces significant challenges, including the absence of implementing government regulations, the lack of an established independent supervisory authority, and the potential for discrepancies between the PDP Law and internationally recognized data protection standards. The lack of legal certainty surrounding the implementation of the PDP Law may impact foreign investment activities in Indonesia. Foreign investors, as data controllers, are required to comply with the provisions of the PDP Law, while at the same time, they need legal clarity to avoid misunderstandings that could lead to sanctions or criminal penalties. This study is conducted in a straightforward manner to address the challenges faced by foreign investors in implementing the PDP Law in Indonesia.